Pengaruh Familiarity dan Usability terhadap Customer Satisfaction serta Customer Loyalty pada Pengguna Facebook (Studi pada Masyarakat Kota Malang) - Muhammad Idham Sofyan; Fatchur Rohman (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The goal of this research is to analyze the pattern of relationship by understanding the direct influence of consumer familiarity and usability of social network (Facebook) to customer satisfaction and loyalty on its users in Malang, East Java. This explanatory research written in a descriptive approach, refer to the theory of decision-making process by Kotler-Keller and Peter-Olson. A critical incident of Facebook are a characteristic of the product and service that the customer would like and which specifically explainable. The critical incident technique is another approach for determining customer requirements by describes satisfaction items and critical incident. Facebook as a product which has a critical incident is analyzed with a few of test related to consumer familiarity and usability. The number of sample is rounded to 130 people. The collected data analyzed by path analysis, with maximum likelihood estimation method. The result findings were: the variable of familiarity and usability significantly influenced customer satisfaction and loyalty. Meanwhile, the variable of customer satisfaction isn’t significantly influenced customer loyalty. For the result, total determinant coefficient on path model is 52%.Keywords: familiarity, usability, satisfaction, loyalty, Facebook